Determining factors influencing cloud services adoption in India - Rastogi, Garima; Verma, Hemraj; Sushil, Rama (Serbian Journal of Management, 2018)
This study identifies the factors influencing cloud services adoption in India using Unified Theory of Acceptance and Use of Technology (UTAUT) model. Role of perceived risk as a moderator in adoption of cloud services, too, has been examined along with other moderators such as gender, age, experience and voluntariness of use as stated in UTAUT model. Following a descriptive research design, a survey was conducted and a structured questionnaire was administered randomly to a sample of 379 respondents in Dehradun region. Most of the relationships confirmed to UTAUT model. Performance expectancy and effort expectancy emerged as the two most significant factors influencing cloud services adoption. Perceived risk, too, played a significant moderating role in adoption of cloud services. Cloud based services are relatively new to consumers in India. The benefits of these cloud technology can only be reaped fully if more and more customers adopt it. Also, various types of risks, such as financial loss, data loss, privacy etc., are associated with using cloud services. Therefore, this study may have immediate implications for cloud service providers.